2012
DOI: 10.1016/j.ces.2012.09.004
|View full text |Cite
|
Sign up to set email alerts
|

The functionalization of carbon nanotubes using a batch oscillatory flow reactor

Abstract: This paper describes an efficient method for the functionalizing of multi-walled carbon nanotubes (MWCNT) using oscillatory flow mixing (OFM). A 3. l batch oscillatory flow reactor (OFR) was designed and constructed for pilot scale functionalization of MWCNT in order to potentially improve their compatibility within a thermoplastic polyphenylene sulphide (PPS) matrix. The OFM batch reactor consisted of a jacketed cylindrical vessel with a vertical axial oscillator that contained a series of baffled mixing plat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 33 publications
0
6
0
2
Order By: Relevance
“…Additionally, while the majority of these applications involved a single orifice baffle design, alternative approaches have also been considered. 178 The OFR has also been examined for continuous applications, see 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 breakage of flow axi-symmetry which was found to be related to the smaller cross-free section of the constrictions in the SPC geometry. Numerical simulations 187 The results of the study showed that the level of back-mixing was highly dependent on both f and x 0 (as with traditional ...…”
Section: Equipmentmentioning
confidence: 97%
“…Additionally, while the majority of these applications involved a single orifice baffle design, alternative approaches have also been considered. 178 The OFR has also been examined for continuous applications, see 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 breakage of flow axi-symmetry which was found to be related to the smaller cross-free section of the constrictions in the SPC geometry. Numerical simulations 187 The results of the study showed that the level of back-mixing was highly dependent on both f and x 0 (as with traditional ...…”
Section: Equipmentmentioning
confidence: 97%
“…Previously, a great deal of research was conducted to overcome the challenges mentioned above; i.e., to improve the dispersion of CNT in the epoxy matrix [16][17][18][19][20][21]. Most techniques deal with processing issues rather than scrutinizing the filler design aspect or architecture.…”
Section: Introductionmentioning
confidence: 97%
“…Most techniques deal with processing issues rather than scrutinizing the filler design aspect or architecture. The research included investigations of different methods such as chemical functionalization [16][17][18][19], physical blending (ultrasonication or high shear mixing) [20,21] and hybridization [22]. Chemical functionalization focuses on the surface treatment of the CNT structure to improve its chemical interaction with the polymer matrix, resulting in enhanced dispersion.…”
Section: Introductionmentioning
confidence: 99%
“…Covalent functionalisation of the CNT surface is considered as another chemical method. The most commonly used covalent functionalisation is through oxidative treatment which attaches oxidised functional groups to the CNT surface, such as carboxylic groups [14][15][16]. This increases the CNTs solubility, because of the generation of a more hydrophilic surface structure, which in turn reduces agglomeration of CNTs [17].…”
mentioning
confidence: 99%